Learning Models to Improved Mathematical Communication Skills - Purwanto, Burhan Eko; Jusmalisa, Icha; Sari, Indah Permata; Jatmiko, Agus; Pasetiyo, Andika Eko (Desimal: Jurnal Matematika, 2020)
The problem faced by students in slow learning is in terms of communication. The use of Auditory, Intellectually, Repetition (AIR) and Cooperative Think Pair Share (TPS) types is needed to help students communicate mathematically in expressing mathematical ideas. This study aims to determine whether or not there are differences in mathematical communication skills of students using the Auditory, Intellectually, Repetition (AIR) learning model with students who use Think Pair Share (TPS) Cooperative learning models. This research uses a quantitative approach using the Quasi Experiment method. The research design is in the form of posttest only, non-equivalent group design. Testing data using the T test with Independent Samples T-Test. Based on the results of hypothesis testing obtained p-value> α 0.05. So it was concluded that there were indications of differences between Auditory, Intellectually, Repetition (AIR) learning models with (TPS) Cooperative learning models and superior (AIR) learning models compared to Cooperative learning models of (TPS) Type in influencing students' mathematical communication skills.